In search of synergy in small group performance - Larson, James R. (Psychology Press, 2010)
"This volume critically evaluates more than a century of empirical research on the effectiveness of small, task-performing groups, and offers a fresh look at the costs and benefits of collaborative work arrangements. The central question taken up by this book is whether - and under what conditions - interaction among group members leads to better performance than would otherwise be achieved simply by combining the separate efforts of an equal number of people who work independently. This question is considered with respect to a range of tasks (idea-generation, problem solving, judgment, and decision-making) and from several different process perspectives (learning and memory, motivation, and member diversity)." "As a framework for assessing the empirical literature, the book introduces the concept of 'synergy'. Synergy refers to an objective gain in performance that is attributable to group interaction. Further, it distinguishes between weak and strong synergy, which are performance gains of different magnitude. The book highlights the currently available empirical evidence for both weak and strong synergy, identifies the conditions that seem necessary to produce each, and suggests where the search for synergy might best be directed in the future." "The book is at once a high-level introduction to the field, a review of the field's history, and a scholarly critique of the current state-of-the-art. As such, it is essential reading for graduate students, advanced undergraduate students, and researchers interested in group dynamics generally - and small group performance in particular."--Book jacket.